ASEAN Competitiveness, Is Indonesia Ready Yet? - Djafar, Zainuddin (Indonesian Journal of International Law, 2012)
What does it mean by ASEAN competitiveness? And, is Indonesia ready for it? These are the questions that have become the main issues to be discussed in this article. Therefore, it is important to note some main key messages introduced by ACI in relation to ASEAN position within its competitiveness and its future prospect, and the dynamic of world economic, such as; ASEAN is facing profound changes in the global economic climate with the rise of China and India and weakened economic prospects in major advanced countries. Besides, this Southeast Asia Regional Organization is also entering a new phase in its cooperation as members move towards building an ASEAN Community by 2015. Thus it is important and urgent for Indonesia to have its priority, and to be ready for its micro and macro competitiveness, that are more advance than the ASEAN 3 (Singapore, Thailand, and Malaysia).